Impact of Foreign Direct Investment on Economic Growth of China after Economic Reform - Majumder, Shapan Chandra; Rahman, Md. Hasanur (Journal of Entrepreneurship, Business and Economics; Vol 8 No 2 (2020), 2020)
After the reformation and open-door policy, the economic and financial expansion of China has been faster than before. This study examines the impact of FDI on economic growth in China empirically. The paper uses time-series data over a period spanning from 1982 – 2019. From the results, FDI and trade have a positive impact on the GDP growth rate. The effects of each of the endogenous variables are examined via the Vector Error Correction Model (VECM). The study shows that there exist long-run associations between the FDI and the growth of GDP in China and short-run causality is found between them Research paper Keywords: FDI; Economic Growth; VECM Model; Economic Reform Reference to this paper should be made as follows: Majumder, S. H., & Rahman, M. H. (2020). Impact of Foreign Direct Investment on Economic Growth of China after Economic Reform, Journal of Entrepreneurship, Business and Economics , 8 (2), 120–153.